Enamel thickness variation in the deciduous dentition of extant large‐bodied hominoids. Issue 3 (7th August 2020) - Ortiz, Alejandra; Schander‐Triplett, Katherine; Bailey, Shara E.; Skinner, Matthew M.; Hublin, Jean‐Jacques; Schwartz, Gary T.
Abstract: Objectives: Enamel thickness features prominently in hominoid evolutionary studies. To date, however, studies of enamel thickness in humans, great apes, and their fossil relatives have focused on the permanent molar row. Comparatively little research effort has been devoted to tissue proportions within deciduous teeth. Here we attempt to fill this gap by documenting enamel thickness variation in the deciduous dentition of extant large‐bodied hominoids. Materials and methods: We used microcomputed tomography to image dental tissues in 80 maxillary and 78 mandibular deciduous premolars of Homo sapiens, Pan troglodytes, Gorilla, and Pongo . Two‐dimensional virtual sections were created from the image volumes to quantify average (AET) and relative (RET) enamel thickness, as well as its distribution across the crown. Results: Our results reveal no significant differences in enamel thickness among the great apes. Unlike the pattern present in permanent molars, Pongo does not stand out as having relatively thicker‐enameled deciduous premolars than P. troglodytes and Gorilla. Humans, on the other hand, possess significantly thicker deciduous premolar enamel in comparison to great apes. Following expectations from masticatory biomechanics, we also find that the "functional" side (protocone, protoconid) of deciduous premolars generally possesses thicker enamel than the "nonfunctional" side. Discussion: Our study lends empirical support to anecdotal observations that patterns of AET and RET observed for permanent molars of large‐bodied apes do not apply to deciduous premolars. By documenting enamel thickness variation in hominoid deciduous teeth, this study provides the comparative context to interpret rates and patterns of wear of deciduous teeth and their utility in life history reconstructions.